TRAF6 Regulates the Immunosuppressive Effects of Myeloid-Derived Suppressor Cells in Tumor-Bearing Host - Song, Ge; Zhang, Yue; Tian, Jie; Ma, Jie; Yin, Kai; Xu, Huaxi; Wang, Shengjun (Frontiers in Immunology, 2021)
Myeloid-derived suppressor cells (MDSCs) are immature heterogeneous cells from the bone marrow and the major component of the tumor-induced immunosuppressive environment. Tumor necrosis factor receptor-associated factor 6 (TRAF6), an E3 ubiquitin ligase, catalyzes the polyubiquitination of target proteins. TRAF6 plays a critical role in regulating the immune system. However, whether TRAF6 is involved in the regulation of MDSCs has not been thoroughly elucidated to date. In this study, we found that the expression of TRAF6 in MDSCs derived from tumor tissue was significantly increased compared with that of MDSCs from the spleens of tumor-bearing mice. Knockdown of TRAF6 significantly attenuated the immunosuppressive effects of MDSCs. Mechanistically, TRAF6 might improve the immunosuppression of MDSCs by mediating K63-linked polyubiquitination and phosphorylation of signal transducer and activator of transcription 3 (STAT3). Additionally, the increased MDSCs in the blood of lung cancer patients were found to express high levels of TRAF6 and arginase 1. There was a positive correlation between the level of TRAF6 and arginase 1. Taken together, our results suggest a critical role for TRAF6 in regulating the immunosuppressive function of MDSCs and provide a potential target for antitumor immunotherapy.